LESSONS LEARNT FROM INAPPROPRIATE D-DIMER TESTING – CASE REPORT - Pantić, Nikola M; Sabljić, Nikica; Bogdanović, Andrija; Jaković, Ljubomir; Mitrović, Mirjana (Srpski medicinski časopis Lekarske komore, 2024)
Introduction: Since the beginning of the COVID-19 pandemic, D-dimer testing has been widely used in not-yet-approved indications. This has led to misdiagnosis, overuse of diagnostic procedures, and unnecessary costs. Case report: Herein, we report the case of a 50-year-old female patient who came to the emergency department with chest pain, shortness of breath, fatigue, and pain in her right leg. Because of an elevated level of D-dimer (4.73 mg/l (N:<0.5)), deep vein thrombosis and pulmonary embolism, as well as COVID-19 were excluded. Therapy with rivaroxaban, 10 mg/day, was initiated. Seven days later, the D-dimer level continued to rise (17.52 mg/l), which was why rivaroxaban was replaced with low molecular weight heparin (LMWH). After another five days, the level of D-dimer continued to rise (27.26 mg/l). A complete blood count revealed significant thrombocytopenia (54 x 109/l). As the 4Ts score for heparin-induced thrombocytopenia was 5, the anti-heparin/PF4 antibody test was performed, and it came back strongly positive (4+). LMWH was replaced with fondaparinux sodium, and the patient was referred to a hematologist. On examination, cutaneous bleeding and gingivorrhagia were present. Laboratory analyses registered pancytopenia (hemoglobin = 101 g/l; white blood cell count = 1.7 x 109/l; platelet count = 29 x 109/l) and consumption coagulopathy (INR = 1.7; aPTT = 27.1 s; fibrinogen = 0.8 g/l; D-dimer = 30.9 mg/l). Bone marrow aspirate was analyzed and the diagnosis of acute monoblastic leukemia, 47, XX, +12 [4] / 46, XX [16], FLT3-ITD, wild-type NPM1, was established. Conclusion: D-dimer is a powerful diagnostic tool when used properly. It should never be treated as a single, isolated result and the decision to introduce anticoagulant therapy should never be made based on its value alone.